Poetry as postmodern - Zhang, Jieqiang (2012)
According to Brian McHale, “Poetry from certain points of view had been postmodern before the postmodern, or had always already been postmodern.” This paper will examine exactly how poetry can be considered to be postmodern. It will undertake a study of Denis Donoghue’s On Eloquence, and attempt to show how Donoghue’s description of literary eloquence correlates with postmodernism, in its yearning for non-referentiality, its impulse for anarchy, its desire for play, its devotion to pleasure, its creation of textual worlds, and its gesture toward language’s metaphoric nature. Since poetry is the textual art that exemplifies literary eloquence the most, it follows that poetry exhibits these postmodern tendencies most clearly, particularly postmodernism's interest in limits, its preoccupation with the metaphysics of absence. The paper will then make a case for how the poetic form is intimately concerned with silence, and thus, is inherently geared toward an exploration of the limits of language: how the poem’s visual shape can be seen as a metaphor for silence, how the poem is actually made of ruins—of the “ruined” poetic verse—and finally, how poetry’s near-condition of music is its desire to detach itself from the real world, into an imaginative textual reality.